Phase 3 Trial of Ibrutinib plus Rituximab in Waldenström’s Macroglobulinemia - Dimopoulos, Meletios A; Tedeschi, Alessandra; Trotman, Judith; García-Sanz, Ramón; Macdonald, David; Leblond, Veronique; Mahe, Beatrice; Herbaux, Charles; Tam, Constantine; Orsucci, Lorella; Palomba, M. Lia; Matous, Jeffrey V; et al. (The New England journal of medicine, 2018)
A randomized trial comparing ibrutinib plus rituximab with rituximab alone in patients with Waldenström’s macroglobulinemia showed significantly higher rates of progression-free survival and overall response with the addition of ibrutinib.